Current concepts of surveillance and its significance in head and neck cancer - Manikantan, Kapila (The Royal College of Surgeons of England, 2011)
Follow-up in head and neck cancer (HNC) is essential to detect and manage locoregional recurrence or metastases, or second primary tumours at the earliest opportunity. A variety of guidelines and investigations have been published in the literature. This has led to oncologists using different guidelines across the globe. The follow-up protocols may have unnecessary investigations that may cause morbidity or discomfort to the patient and may have significant cost implications. In this evidence-based review we have tried to evaluate and address important issues like the frequency of follow-up visits, clinical and imaging strategies adopted, and biochemical methods used for the purpose. This review summarises strategies for follow-up, imaging modalities and key investigations in the literature published between 1980 and 2009. A set of recommendations is also presented for cost-effective, simple yet efficient surveillance in patients with head and neck cancer.